1992
DOI: 10.1001/jama.1992.03490150102032
|View full text |Cite
|
Sign up to set email alerts
|

Physicians' Utilization and Charges for Outpatient Diagnostic Imaging in a Medicare Population

Abstract: Nonradiologist physicians who operate diagnostic imaging equipment in their offices perform imaging examinations more frequently, resulting in higher imaging charges per episode of medical care. These results extend our previous research on this subject by their focus on a broader range of clinical presentations; a mostly elderly, retired population; and the inclusion of higher-technology imaging examinations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
44
0
1

Year Published

1993
1993
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 161 publications
(46 citation statements)
references
References 7 publications
1
44
0
1
Order By: Relevance
“…Schroeder (1992), for instance, looking at the situation in the United States, showed that a greater number of surgical specialists was associated with a relatively high utilization of surgical procedures. Moreover, Crane (1992), Hillman et al (1992), and Mitchell and Scott (1992) showed that physicians who own diagnostic imaging equipment were more likely to order tests than were physicians who did not own such equipment. In fact, many U.S. states have restricted self-referrals by physicians who own imaging equipment.…”
Section: Previous Studiesmentioning
confidence: 99%
“…Schroeder (1992), for instance, looking at the situation in the United States, showed that a greater number of surgical specialists was associated with a relatively high utilization of surgical procedures. Moreover, Crane (1992), Hillman et al (1992), and Mitchell and Scott (1992) showed that physicians who own diagnostic imaging equipment were more likely to order tests than were physicians who did not own such equipment. In fact, many U.S. states have restricted self-referrals by physicians who own imaging equipment.…”
Section: Previous Studiesmentioning
confidence: 99%
“…Self-referral is associated with as much as a seven-fold increase in utilization of xrays, computed tomography scans, and myocardial perfusion imaging. [15][16][17][18][19] Mitchell and Sass have postulated that both financial and quality incentives drive physicians to both install and utilize on-site ancillary services. 25 Financially, offices that have onsite laboratories may be able to bill not only for phlebotomy but also the processing of each test.…”
Section: Commentmentioning
confidence: 99%
“…10 Recent studies have found that self-referral for imaging is increasing [11][12][13][14] with several studies showing that physicians who own diagnostic imaging equipment order more tests. [15][16][17][18][19] There are no recent studies examining test ordering by physicians who maintain on-site laboratories.…”
Section: Introductionmentioning
confidence: 99%
“…The authors concluded that the differences could not be attributed to the physicians' specialty or the diagnostic classifications of the patients (Hillman et al, 1990). Hillman et al (1992) compared charges and utilization of diagnostic imaging in a broad range of clinical presentations and found that physicians who own imaging technology employ imaging significantly more often than do physicians who refer their imaging examinations to non-entity radiologists. The study also found charges to be 1.6 to 6.2 times higher in the physician owned groups (1992).…”
Section: Studies On Joint-ventures and Self-referralmentioning
confidence: 99%